2015
DOI: 10.1007/s10916-015-0331-2
|View full text |Cite
|
Sign up to set email alerts
|

New Authentication Scheme for Wireless Body Area Networks Using the Bilinear Pairing

Abstract: Due to the development of information technologies and network technologies, healthcare systems have been employed in many countries. As an important part of healthcare systems, the wireless body area network (WBAN) could bring convenience to both patients and physicians because it could help physicians to monitor patients' physiological values remotely. It is essential to ensure secure communication in WBANs because patients' physiological values are very sensitive. Recently, Liu et al. proposed an efficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
94
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(94 citation statements)
references
References 27 publications
0
94
0
Order By: Relevance
“…Unfortunately, the limited computing capability and battery capacity of the mobile device hinders the application of TPKC in implantable medical system. The concept of ECC (Elliptic curve cryptosystem) was then put forward [22] which provided the same security with a much smaller key size compare to the TPKC [23] so that many ECC-based protocols were proposed subsequently [13,24]. In 2013, Liu et al [25] put forward a scheme in which they used the bilinear pairing defined on the elliptic curve to design a new certificateless signature scheme, but later in 2014, Xiong [26] analyzed the Liu et al 's authentication protocol and concluded that their scheme was prone to a kind of attack by a key replacement adversary [27].…”
Section: Related Workmentioning
confidence: 99%
“…Unfortunately, the limited computing capability and battery capacity of the mobile device hinders the application of TPKC in implantable medical system. The concept of ECC (Elliptic curve cryptosystem) was then put forward [22] which provided the same security with a much smaller key size compare to the TPKC [23] so that many ECC-based protocols were proposed subsequently [13,24]. In 2013, Liu et al [25] put forward a scheme in which they used the bilinear pairing defined on the elliptic curve to design a new certificateless signature scheme, but later in 2014, Xiong [26] analyzed the Liu et al 's authentication protocol and concluded that their scheme was prone to a kind of attack by a key replacement adversary [27].…”
Section: Related Workmentioning
confidence: 99%
“…To improve security and efficiency, Zhao proposed an identity-based efficient anonymous authentication scheme for WBANs. However, Zhao's scheme cannot provide real anonymity because the users' pseudo identities are constant value and the adversary could tract the users; then Wang and Zhang proposed a new anonymous authentication scheme for WBANs [18]. Security analysis shows that the proposed scheme could overcome weakness in previous scheme.…”
Section: Related Workmentioning
confidence: 99%
“…An anonymous authentication scheme is proposed in [78] by Wang and Jang, which applies three participants in the authentication process that are client, network manager, and application provider. The network manager is a trusted third party, and the manager is responsible for producing private keys for the clients and the application provider.…”
Section: Anonymous Authenticationmentioning
confidence: 99%